Analysis of Catastrophic Health Financing by Key Institutions - Alvin B. Caballes (Philippine Institute for Development Studies (PIDS), 2014)
Financial protection of patients is considered a key component of health systems, and has been a consistent policy goal of the Department of Health. Of paramount importance in this regard are catastrophic health expenditures, which can severely restrict the access to much-needed services, contribute to (further) impoverishment, or result in both, for the affected patients and families. This study was undertaken to determine the institutional mechanisms for addressing these expenditures, and develop a framework to improve the existing arrangements. Focus group discussions (FGDs) and consultations were conducted for this study.Based on the inputs from the FGDs, the following recommendations are made: (1) A new definition of catastrophic health expenditures is proposed thus: "The situation applies when a patientâs condition requires medical interventions which are life or limb saving and determined to be clinically appropriate and cost effective, but attendant expenses are beyond the actual means of the patient (or family) at the time of need, whether due to time or resource constraints"; (2) The burden of financial support will be assigned to specific agencies, depending on care requirements (e.g., facilities to absorb costs of urgent care to be subsequently reimbursed by third-party payers; PhilHealth and PCSO to attend to intensive care; and PhilHealth and DSWD to finance chronic care); and (3) A dedicated unit will be established to further develop relevant policies and strategies for the integrated financing of catastrophic health expenditures.
Keywords: 330; Philippines; universal health care (UHC); catastrophic health expenditure; financial risk protection